DIGITAL TRANSFORMATION OF THE FASHION INDUSTRY: KEY TECHNOLOGICAL TRENDS AND INNOVATIONS - MYTSA, VIKTORIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The modern fashion industry is undergoing radical changes under the influence of digital transformation, which is revolutionizing the fashion industry. Digital technologies open up new opportunities for creators, brands and consumers. And to remain competitive, it is necessary to adapt to them. The implementation of digital innovations will transform every element of this system. The paper analyzes the key aspects of the digital transformation of the fashion industry. Art in the context of digital transformation acquires new forms of expression thanks to the introduction of virtual (VR) and augmented reality (AR), creation of NFT collections of clothes and accessories. Fashion design is being transformed through the use of 3D modeling and digital design tools. Production in the era of digitalization is characterized by the introduction of Industry 4.0 technologies. Branding in the digital age is being transformed by big data and AI technologies that enable personalized marketing strategies and improved customer interactions. Retail trade is undergoing the most visible changes under the influence of digitalization. E-commerce, mobile apps and omnichannel sales strategies are becoming the norm. Since digital transformation is a continuous process, after solving one problem, companies must move on to the next, constantly adapting to new challenges and market opportunities. The proposed recommendations for the implementation of digital technologies take into account the specifics of fashion business segments and are aimed at increasing the competitiveness, efficiency and innovation of companies in the conditions of digital transformation in the fashion industry. The recommended approach to digital transformation, focused on solving specific problems, emphasizes the need for flexibility and adaptability and allows to ensure the maximum efficiency of innovation implementation.